Cover Image. Issue 8 (5th July 2017) - Zimmermann, Kaeli; Walz, Christina; Derckx, Raissa T; Kendrick, Keith M.; Weber, Bernd; Dore, Bruce; Ochsner, Kevin N.; Hurlemann, René; Becker, Benjamin
Abstract : COVER ILLUSTRATION: Marijuana users display impaired cognitive regulation of negative emotions paralleled by increased frontal activity and decreased amygdala‐prefrontal connectivity.